Analysis of longitudinal cracked two-dimensional functionally graded beams exhibiting material non-linearity (Fracture and Structural Integrity, 2017)
An analytical study of longitudinal fracture in two-dimensional functionally graded cantilever beam configurations is carried-out with taking into account the non-linear behavior of material. A longitudinal crack is located arbitrary along the beam cross-section height. The material is functionally graded along the width as well as along the height of beam. The external loading consists of a bending moment applied at the free end of lower crack arm. Fracture is studied in terms of the strain energy release rate by considering the beam complementary strain energy. The solution derived is verified by analyzing the longitudinal crack with the help of the J-integral. The distribution of J-integral value along the crack front is studied. The effects of crack location, material gradients and non-linear behavior of material on the fracture are elucidated. The analysis reveals that the material non-linearity has to be taken into account in fracture mechanics based safety design of structural members and components made of two-dimensional functionally graded materials.
Keywords: Functionally graded beam; Crack; Material non-linearity; Analytical solution